Analysis of the effect of different intensities and rest interval on the perceived exertion of athletes - V.O. Damasceno; M.R. Mota; T.S. Silva; M.S. Silva; F. Martins da Silva (Desafio Singular, 2011)
The research examined the effects of different intensities and different rest intervals of strength training on the rating of perceived exertion (RPE) in young athletes. Participated in the study 23 young men, aged 17.06 ± .73 years, 68.01 ± 8.09 kg of body mass, and 173.65 5.61 cm of height. They were submitted to the appropriateness of charges (5 RM, 10 RM or 15 RM) and rest intervals (30, 60 or 120 s) and then asked to point perceived exertion according to the OMNI-RES scale. A two-way ANOVA was used and significant differences were analyzed by post-hoc Bonferroni. For RPE there were no significant differences between the intensities in the recovery intervals evaluated. For intervals with the same intensity, there were differences between 15 RM and range of 120 and 60 s with 15 RM and 30 s intervals. Intensities of 10 and 5 RM, in the range of 120 s showed significant differences. It follows that the smaller the rest interval the greater the levels of fatigue regardless of the number of repetitions performed in all intensities and it may be inferred that the RPE was sensitive to reduction in the rest interval.